2014
DOI: 10.1007/s10113-014-0672-2
|View full text |Cite
|
Sign up to set email alerts
|

Grassland farmers’ attitudes toward climate change in the North German Plain

Abstract: The impact of climate change on a variety of scales and on land-use policies across sectors is well-established. There will be climate-related changes to which land use must adapt, although Europe and Germany may not be as affected as other regions. Therefore, we must evaluate how climate change is perceived on a regional scale and across land-use sectors. The aim of this study is to gather information from regional land-use experts regarding their perceptions of climate change to highlight the impact of clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…For instance, Eggers et al . () find 67 per cent of German farmers at least partially agree that climate change had an influence on their agricultural production; indicating they likely believe climate change is occurring.…”
Section: Understandings Of Farmers’ Perception Of Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Eggers et al . () find 67 per cent of German farmers at least partially agree that climate change had an influence on their agricultural production; indicating they likely believe climate change is occurring.…”
Section: Understandings Of Farmers’ Perception Of Climate Changementioning
confidence: 99%
“…This includes: Germany (67 per cent) (Eggers et al . ), Australia (68 per cent) and regions of New Zealand (51–53 per cent) (Prokopy et al 2015); Scotland (58 per cent) (Barnes and Toma ), and states throughout the USA (Gramig et al . ; Niles et al .…”
Section: Understandings Of Farmers’ Perception Of Climate Changementioning
confidence: 99%
“…The RCP 8.5 scenario estimates an increase of the global mean screen temperature of approximately 5.3°C in the time period 1850-2090. Considering the RCP 8.5 scenario was a joint decision of the NaLaMa-nT consortium (Albert et al, 2015;Eggers et al, 2015).…”
Section: Climate Datamentioning
confidence: 99%
“…Eggers et al (2014) found that North German grassland farmers could be grouped into four types based on their perceptions of the issue. The research, which focuses on adaptation measures on ley and permanent grassland, postulates that farmers consider adaptation on economic factors or emotional reasoning.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other groupings did not perceive climate change as a significant enough threat to change their future management planning. Whereas these studies have focused on farmer types in other sectors, or on one aspect of adaptation or mitigation (Eggers et al 2014;Bruce 2013), there is a specific need to investigate beef and sheep farmers' perceptions of climate change in temperate regions. Such analyses are important in light of the considerable attention bestowed on the red meat sectors' contribution towards climate change; therein, assisting the industry's aspirations in reducing emissions.…”
Section: Introductionmentioning
confidence: 99%